COFFEE PRODUCTION IN THE BRAZILIAN SAVANNAH: CONSIDERATIONS ABOUT NITROGEN NUTRITION - Pereira Bruno, Isabeli; Meriguetti Pinto, Victor; Reichardt, Klaus (REVISTA DE AGRICULTURA, 2020)
The Brazilian savannah, locally called â€œcerradoâ€, is a forest and shrub type ecosystem that occupied vast areas of very flat relief, mainly distributed in the central part of the country. In the mid 1970ies, this region was recognized as unfertile with little possibility of agricultural use. From there on, a large part of this biome was occupied by extensive agricultural production, due to the advances in technology. The coffee crop is very important for the Brazilian agribusiness, and in recent years, part of its cultivation has been shifted from the traditional growing areas (e.g. SÃ£o Paulo and southern of Minas Gerais) to some cerrado areas (e.g. northwestern of Minas Gerais and western of Bahia). Cerrado has quite different edaphoclimatic conditions than the traditional coffee regions, and therefore crop management should be re-evaluated, including those concerning the nitrogen. This paper aims to review some studies already carried out on nitrogen fertilization in cerrado coffee plantations.